(untitled) (London, 2016)
A leading textbook in its field, Human Resource Management at Work provides a clear introduction to the multiple meanings of HRM and the relationship between strategy and HRM. Covering international and comparative HRM as well as HRM and performance, it is filled with case studies and activities to bring the subject to life while summarizing the major forces shaping HRM and looking at the principal theoretical frameworks.
Keywords: Quản trị nhân sự,Personnel management